POLICY MODEL FOR POST-MINING VILLAGE DEVELOPMENT GOVERNANCE TO ACHIEVE THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN BANGKA REGENCY - Zamzani Zamzani; Alfitri; Andries Lionardo; Abdul Nadjib (SOSIOEDUKASI, 2026)
This study examines policy and governance in post-mining village development to support the Sustainable Development Goals (SDGs) in Bangka Regency. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving government officials, village leaders, facilitators, community representatives, beneficiaries, and mining companies. Data were analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that post-mining village development has progressed through the stages of agenda setting, formulation, adoption, and implementation. However, implementation remains suboptimal due to the absence of a comprehensive policy specifically regulating post-mining village development. Governance practices reflect actor interdependence, resource exchange, shared rules, and network autonomy, but are constrained by weak coordination, limited institutional capacity, dependency on corporate support, and insufficient environmental integration. Supporting factors include government commitment, community participation, village facilitators, Village SDGs, CSR programs, and social capital. The study proposes the Collaborative Sustainable Post-Mining Village Governance (CSPMVG) Model, integrating policy processes, collaborative governance, and sustainable development principles.